Eficiencia de la cáscara de huevo como catalizador para la obtención de biodiesel a partir de la grasa de pollo. - Cuenca Vaca, Ariana Briseth; Espinoza Loja, Bryan Manuel (My University, 2024)
The objective of this research work is to evaluate the efficiency of eggshell as a basic heterogeneous catalyst based on calcium oxide (CaO) applied in the process of transesterification of chicken fat to obtain biodiesel, an alternative proposed for the circular economy of the poultry sector. Eggshell, having a high percentage of calcium carbonate (CaCO3), is subjected to a calcination process for its conversion into calcium oxide (CaO), a compound that has demonstrated a catalytic nature in processes where heterogeneous alkaline catalysts are applied. To obtain it, three tests were carried out at different time and temperature conditions, 3 hours at 800 ºC; 4 hours at 900 ºC; 5 hours at 1000 ºC, these were subjected to manual agitation using 80 cm crucible tongs every 10 seconds at 1 hour intervals since the muffle reached its established temperature. The chicken fats obtained were treated to eliminate impurities and subsequently subjected to a wet rendering process for a higher percentage of oil extraction. This oil entered an esterification process in order to reduce free fatty acids to prevent saponification. Characterization analyses were performed which determined an acid index (AI) of 0.7005 mg NaOH/g ≤ 1, free fatty acids (FFA) of 0.304% ≤ 2.54%, demonstrating optimal conditions for subsequent transesterification. According to the catalyst characterization, the X-ray diffraction (XRD) analysis presented a 90% similarity to pattern 00-048-1467 at 900 °C conditions for 4 h, of treatment with CaO patterns when comparing their intensity peaks. The images taken by scanning electron microscope (FEM-SEM) showed cubic crystalline species of high porosity with a particle size ≤ 5 µm and agglomerations of about 50 µm in length, in addition, with the help of an energy dispersive X-ray spectroscopy (EDS) sensor, the mass composition of 67.6728% oxygen and 51.6298% calcium was determined. For the experimental model of the transesterification process, the catalyst loading by weight (2%, 3% and 4%) and the methanol-oil molar ratio (6:1, 9:1 and 12:1) were evaluated as independent variables at conditions of 65°C and 300 rpm, with the objective of determining the optimum conditions to maximize the yield in obtaining biodiesel. The results showed that the highest conversion (96.3%) was achieved with 3% catalyst and 9:1 molar ratio, confirming the feasibility of the agro-industrial waste revalorization process. The ANOVA analysis resolved with a p-value of 0.0009, validating the efficiency of the catalyst obtained for obtaining biodiesel with the experimental design determined.
El presente trabajo de investigación tiene como objetivo evaluar la eficiencia de la cáscara de huevo como un catalizador básico heterogéneo a base de óxido de calcio (CaO) aplicado en el proceso de transesterificación de la grasa de pollo para la obtención de biodiesel alternativa propuesta para la economía circular del sector avícola. La cascara de huevo al tener un alto porcentaje de carbonato de calcio (CaCO3) es sometida a un proceso de calcinación para su conversión en óxido de calcio (CaO), compuesto que ha demostrado una naturaleza catalítica en procesos donde se aplican catalizadores alcalinos heterogéneos. Para su obtención se realizó tres pruebas a diferentes condiciones de tiempo y temperatura, 3 horas a 800 ºC; 4 horas a 900 ºC; 5 horas a 1000 ºC, estas fueron sometidas a una agitación manual utilizando pinzas para crisol de 80 cm cada 10 segundos en intervalos de 1 hora desde que la mufla llega a su temperatura establecida. Las grasas de pollo obtenidas fueron tratadas para eliminar impurezas y posteriormente sometidas a un proceso de renderización húmeda para un mayor porcentaje de extracción del aceite. Este aceite ingresó a un proceso de esterificación con la finalidad de reducir los ácidos grasos libres para evitar que exista una saponificación. Se realizaron análisis de caracterización que determinaron un índice de acidez (IA) de 0,7005 mg NaOH/g ≤ 1, ácidos grasos libres (AGL) de 0,304% ≤ 2,54%, demostrando condiciones óptimas para su posterior transesterificación. De acuerdo con la caracterización del catalizador, el análisis de difracción de rayos X (XRD) presentó una similitud del 90% al patrón 00-048-1467 a condiciones de 900 °C por 4 h, de tratamiento con patrones de CaO al comparar sus picos de intensidad. Las imágenes tomadas por el microscopio electrónico de barrido (FEM-SEM) mostraron especies cristalinas cúbicas de alta porosidad con un tamaño de partícula ≤ 5 µm y aglomeraciones de alrededor de 50 µm de longitud, además, con ayuda de un sensor Espectroscopia de rayos X de energía dispersiva (EDS) se determinó la composición en masa de 67,6728% de oxígeno y 51,6298% de calcio. Para el modelo experimental del proceso de transesterificación se evaluaron como variables independientes la carga de catalizador en peso (2%, 3% y 4%) y la relación molar metanol-aceite (6:1, 9:1 y 12:1) a condiciones de 65°C y 300 rpm, con el objetivo de determinar las condiciones óptimas para maximizar el rendimiento en la obtención de biodiesel. Los resultados mostraron que la mayor conversión (96,3%) se alcanzó con un 3% de catalizador y una relación molar 9:1, confirmando la viabilidad del proceso de revalorización de residuos agroindustriales. El análisis ANOVA resolvió con un p-valor de 0,0009, validando la eficiencia del catalizador obtenido para la obtención de biodiésel con el diseño experimental determinado.
Keywords: CASCARA DE HUEVO; OXIDO DE CALCIO; CATALIZADOR; GRASA DE POLLO